AI-powered language learning: A blessing or a curse for English language education? - Nihta Vera Frelly Liando; Devilito Prasetyo Tatipang; Rinny Rorimpandey; Tirza Kumayas; Khalifatun Saudah; Ishak Iskandar (Universitas Syiah Kuala, 2025)
Integrating Artificial Intelligence (AI) into English language learning has garnered substantial attention and raised pertinent questions about its implications for the future of language education. This qualitative study with a systematic review design probes into the complex relationship between AI and English learning, whether AI in English language learning constitutes a potential detriment to the educational process, and whether AI is a disaster or a boon for English learning. A total of 15 peer-reviewed articles published between 2019 to 2023 (indexed in Scopus, WoS, and Sinta) were analyzed through four steps (data extraction, quality assessment, data synthesis, and result interpretation) to ensure comprehensive coverage. The findings from this study revealed not only multifaceted insights into the relationship between AI and English language learning, such as personalized learning, increased interactivity, and accessibility, but also its challenges, including privacy-related concerns, loss of human interactions, and reliability issues. This present study contributes to a comprehensive understanding of the role of AI in English language learning, offering educators, researchers, and policy-makers valuable insights into the benefits and potential pitfalls of integrating AI technologies in language education. Moreover, this present study provides a details exploration of the AI-English learning paradigm, emphasizing the need for a holistic perspective that leverages AIs strengths while safeguarding the integrity and vitality of the English language learning experience. Furthermore, this study offers recommendations for future research endeavors, emphasizing the need for ongoing evaluation and refinement of AI-based English learning strategies.